Anaerobic contribution during maximal anaerobic running test: correlation with maximal accumulated oxygen deficit - Zagatto, A.; Redkva, P.; Loures, J.; Kalva Filho, C.; Franco, V.; Kaminagakura, E.; Papoti, M. [UNESP] (Wiley-Blackwell, 2011)
The aims of this study were: (i) to measure energy system contributions in maximal anaerobic running test (MART); and (ii) to verify any correlation between MART and maximal accumulated oxygen deficit (MAOD). Eleven members of the armed forces were recruited for this study. Participants performed MART and MAOD, both accomplished on a treadmill. MART consisted of intermittent exercise, 20 s effort with 100 s recovery, after each spell of effort exercise. Energy system contributions by MART were also determined by excess post-exercise oxygen consumption, lactate response, and oxygen uptake measurements. MAOD was determined by five submaximal intensities and one supramaximal intensity exercises corresponding to 120% at maximal oxygen uptake intensity. Energy system contributions were 65.4 +/- 1.1% to aerobic; 29.5 +/- 1.1% to anaerobic a-lactic; and 5.1 +/- 0.5% to anaerobic lactic system throughout the whole test, while only during effort periods the anaerobic contribution corresponded to 73.5 +/- 1.0%. Maximal power found in MART corresponded to 111.25 +/- 1.33 mL/kg/min but did not significantly correlate with MAOD (4.69 +/- 0.30 L and 70.85 +/- 4.73 mL/kg). We concluded that the anaerobic a-lactic system is the main energy system in MART efforts and this test did not significantly correlate to MAOD.
Keywords: oxygen uptake peak; anaerobic capacity; blood lactate; running